N+4-6n+3=

Simple and best practice solution for N+4-6n+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for N+4-6n+3= equation:


Simplifying
N + 4 + -6n + 3 = 0

Reorder the terms:
4 + 3 + N + -6n = 0

Combine like terms: 4 + 3 = 7
7 + N + -6n = 0

Solving
7 + N + -6n = 0

Solving for variable 'N'.

Move all terms containing N to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + N + -7 + -6n = 0 + -7

Reorder the terms:
7 + -7 + N + -6n = 0 + -7

Combine like terms: 7 + -7 = 0
0 + N + -6n = 0 + -7
N + -6n = 0 + -7

Combine like terms: 0 + -7 = -7
N + -6n = -7

Add '6n' to each side of the equation.
N + -6n + 6n = -7 + 6n

Combine like terms: -6n + 6n = 0
N + 0 = -7 + 6n
N = -7 + 6n

Simplifying
N = -7 + 6n

See similar equations:

| (2x+8)=116 | | J+184.06=317.91 | | (x^3-3x+1)-(x^3+7-12x)= | | r^2-16r+39=0 | | 2x^2-4=8x | | -34+37+17=x | | 14-2x+4x=14 | | 5x^3-17x^2-12x=0 | | -16-7x=-30 | | -7mr(12m-7r+5)=0 | | -4(-5-b)=0.3(b+16) | | y=6(4(3^1/2)) | | 4(2x-4)-x+5=79 | | -5x+5(-x+3)=115 | | -9z^2+9z-2=0 | | 6(3x+4)+2x-4=100 | | 7-(-6)-8+3=x | | (2y)(4y^3)+(3y^2)(5y^2)=0 | | -5y+2x=10x+15 | | -14.16r=433.44 | | 4-x^2=16 | | X/5=85/30 | | 6=2/5m | | 4y-6=1.5x+4 | | 3x^3-24(6x)=0 | | (A+9)(a^2-9a+3)= | | 4(n+6)=48 | | 4(3x+5)=50 | | 7.3y-5.18=-51.8 | | 4v-9=7 | | 2lnx^2= | | 153=(2x+8)+(7x-2) |

Equations solver categories